THE PRIVILEGE OF KNOWING GOD: RE-LINKS IN TIMES OF CRISIS (Isagoge - Journal of Humanities and Social Sciences, 2022)
Investigating from God, for God and about God is an immense commitment, in which I go in the first person, with my sentiments and a transmethodical investigation with the transmethod of comprehensive, ecosophical and diatopic hermeneutics; going through the analytical, empirical and purposeful moments. It is a responsibility, as long as the insult to the name of God, the separation of the human being, the abuse in colonial solsyadoras religions has compromised the complex understanding of the human being: nature-body-mind-soul-spirit-God. Thus, we return with ecosophia, the wisdom in the art of inhabiting the planet, resorting to the ancient philosophy that dictates that reason is not only located in the mind; but in the soul and the spirit to analyze, in the needs of the planet, in the moral crisis, in the greatest urgency of inhumanity, the privilege of knowing God with re-ligations in times of crisis, this is the complex objective of the inquiry. Diatopia tends to unite topoi separated for convenience in the human being, such as: God-human being, nature-Human Being. In propositional moments, we help so that beyond man's arrogance he thinks of his transcendence. God opens doors for us, we cannot miss the opportunity to enter. Let's go ahead with Him. Praised be his name of love Jesus Christ always in my life, parting the Red Sea to enter through your wide door the door of God. The crisis of civilization will not improve significantly; we must think about changes that lead us to the salvation of our soul and spirit. If you acknowledge Jesus Christ our Lord, dying for us; you can know the Holy Spirit; that in the three divine persons they are inseparable. Science must return to the union with philosophy and this with theology, with cogitative re-linkages of a high level, decolonial and complex.
Keywords: Dios. Ecosófia. Re-ligajes